Artificial Intelligence Efficiency during COVID-19 Pandemic - Tawafak R.M.; Alfarsi G.; Alsideiri A. (Institute of Electrical and Electronics Engineers Inc., 2023)
Artificial intelligence; Breakings; Coronaviruses; Formal education; Mechanical; On-line education; Research facilities; Technology; Virtual research; COVID-19